2020
DOI: 10.1002/14651858.cd004916.pub4
|View full text |Cite
|
Sign up to set email alerts
|

Interventions to slow progression of myopia in children

Abstract: Background-Nearsightedness (myopia) causes blurry vision when looking at distant objects. Highly nearsighted people are at greater risk of several vision-threatening problems such as retinal detachments, choroidal atrophy, cataracts and glaucoma. Interventions that have been explored to slow the progression of myopia include bifocal spectacles, cycloplegic drops, intraocular pressurelowering drugs, muscarinic receptor antagonists and contact lenses. The purpose of this review was to systematically assess the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
159
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 146 publications
(166 citation statements)
references
References 258 publications
4
159
0
3
Order By: Relevance
“…Here, we review some of the key studies, nearly all of which have been published in the past 20 years, with many in the last decade. The rapid pace with which this field is moving is demonstrated by the 2011 systematic review 21 sponsored by Cochrane that concludes:
The most likely effective treatment to slow myopia progression thus far is anti‐muscarinic topical medication……Further information is required for other methods of myopia control, such as the use of corneal reshaping contact lenses or bifocal soft contact lenses with a distance center are promising, but currently no published randomized clinical trials exist.
This statement was based on evidence available in the literature as of October 2011, and as we discuss below, much has happened since then. Although an update was published in 2020, 22 it only includes publications through February 2018 and thus does not include several important recent clinical trials 18,23–27 …”
Section: How Effective Are Various Methods Of Myopia Control?mentioning
confidence: 99%
“…Here, we review some of the key studies, nearly all of which have been published in the past 20 years, with many in the last decade. The rapid pace with which this field is moving is demonstrated by the 2011 systematic review 21 sponsored by Cochrane that concludes:
The most likely effective treatment to slow myopia progression thus far is anti‐muscarinic topical medication……Further information is required for other methods of myopia control, such as the use of corneal reshaping contact lenses or bifocal soft contact lenses with a distance center are promising, but currently no published randomized clinical trials exist.
This statement was based on evidence available in the literature as of October 2011, and as we discuss below, much has happened since then. Although an update was published in 2020, 22 it only includes publications through February 2018 and thus does not include several important recent clinical trials 18,23–27 …”
Section: How Effective Are Various Methods Of Myopia Control?mentioning
confidence: 99%
“…A Cochrane review of the interventions to control myopia progression in children concluded that atropine was the only treatment showing a significant efficacy compared with placebo (Walline et al. ).…”
Section: Introductionmentioning
confidence: 99%
“…To date, multiple randomized controlled trials have provided a good evidence base for the use of atropine as a promising solution in slowing down myopic deterioration in children (Walline et al. ; Wu et al. ; Fang et al.…”
Section: Introductionmentioning
confidence: 99%